A dual input single output non-isolated DC-DC converter for multiple sources electric vehicle applications - Karthikeyan, B; Sundararaju, K; Palanisamy, R; Manivasagam, R; Hossain, Ismail; Bajaj, Mohit; Shouran, Mokhtar; Abdul samad, Bdereddin; Kamel, Salah (Frontiers in Energy Research, 2022)
There is a need to design DC-DC converters capable of handling high voltages and that employ single-stage conversion to integrate renewable energy resources, such as solar photovoltaic cells and fuel cells, for electric vehicle applications. This paper elucidates the design and analysis of a dual input single output non-isolated Cuk-derived converter with a high step-up ratio. The proposed converter can effectively handle two different energy resources that have different electrical characteristics. It makes use of one common inductor between the dual input port, which reduces the passive components and the circuit volume required. The maximum efficiency that can be achieved by this converter is 95.72%, with two main switches and one diode in the circuit. This study involved a detailed analysis of the proposed converter in continuous current operation mode. A continuous current with reduced ripple in the output improves a fuel cell’s operating life-span. The efficacy of the proposed converter is verified through simulation and validated by constructing a 200 W, real-time, scaled-down prototype model.